Mother Teresa - Chawla, Navin (Gurgaon Pengiun Random House, 2016)
This inspirational and heart-warming book details the profound impact that Mother Teresa$1 (Bs life, mission and principles have had on the world. With many a moving anecdotes, from her talk with heads of state for world peace to her poignant prayers for a dying child, this definitive biography gives an inimitable insight into the life of one of the most admired women in the world.s
Keywords: Teresa, Mother, Saint, 1910-1997; Biography; IAS as author; 1969 Batch